School of French - M. K. Ogorodov (Vestnik MGIMO-Universiteta)
Fundamentals of teaching French at MGIMO were laid in the 1950s - 1960s, the teachers of the Department of Romance Languages uniform. Initially, the core department of the French language teachers were MSU: Olga D. Andreeva, Simon I. Ganionsky, Sophia Yulevna Friedman, Irina B. Chachkhiani. Heads of departments of the period the greatest contribution to the development of philological science and practice of teaching Romance languages made an outstanding figure of Russian Romance Studies, Doctor of Philology, Professor Vladimir G. Gak. In 1971, after the separation of the Department of Romance languages were the departments of French and № 1 № 2. At the Department of French № 1 was successfully completed the task of developing a set of textbooks for the initial stage of training French language and created books that have become "classics of the genre".